ASSESSMENT OF SUBSTRATE SOLUTION EXTRACTION METHODS FOR DETERMINATION OF CHEMICAL ATTRIBUTES IN SOILLESS CULTURE OF BELL PEPPER AND MELON - Wamser, Anderson Fernando; Filho, Arthur Bernardes Cecílio [UNESP]; Nascimento, Camila Seno [UNESP]; Nascimento, Carolina Seno [UNESP]; Cortez, Juan Waldir Mendoza; Nowaki, Rodrigo Hiyoshi Dalmazzo [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of this study was to evaluate the efficiency of the porous ceramic cup extractors, associated with ion meters, for the determination of nutrients availability for bell pepper and melon crops in substrate. Substrate solution was acquired using aqueous extract 1:1.5 (v/v) and also the porous ceramic cup extractor. Electrical conductivity (EC), pH and macronutrient contents were determined for the substrate solution through analytical method. The concentrations of NO3- and K+ in the solutions obtained with porous ceramic cup extractors, and the N and K contents in the diagnostic leaf for nutritional evaluation were also determined. The concentrations of NO3- and K+ using the porous ceramic cup extractors have strong correlation (r=0.96 and 0.92, respectively) with the ones obtained using the standard method, as well as a moderate correlation (r=0.65) and a strong one (r=0.71) with contents of N and K, respectively, in the melon diagnostic leaf; and a weak correlation (r=0.36 and 0.26, respectively) in the bell pepper diagnostic leaf. The use of porous ceramic cup extractors for obtaining the substrate solution and the determination of the N-NO3- and K+ contents by means of specific ion meters are a fast method of evaluating nutrients availability in soilless cultures.
AVALIAÇÃO DE MÉTODOS DE EXTRAÇÃO DA SOLUÇÃO DO SUBSTRATO PARA DETERMINAÇÃO DE ATRIBUTOS QUÍMICOS EM CULTIVO SEM SOLO DE PIMENTÃO E MELÃO
Keywords: Aqueous extract; Capsicum annuum L; Cucumis melo L; Plant nutrition